Barium zirconate ceramics for melt processing of barium cuprate superconductors - Kirby, Nigel Matthew (Curtin University, 2003)
The widespread use of high temperature superconductors through improved understanding of their underlying physics is in part dependent on the synthesis of large, high quality single crystals for physical research. Crucible corrosion is an important factor hindering the routine synthesis of large, high purity rare-earth barium cuprate superconductor single crystals. Molten BaCuO2-CuO fluxes required for the growth of such crystals are highly corrosive to substrate materials, and corrosion products may lead to chemical contamination of crystals and other practical difficulties. BaZrO3 is known to be inert to BaCuO2-CuO melts, but its use has remained restricted to a very small number of laboratories worldwide because it is very sensitive to the effects of off- stoichiometric or residual secondary phases which degrade its performance. BaZrO3 suitable for sustained melt containment is difficult to produce due to kinetic limitations of phase purity, difficulty in sintering to adequate density, and very narrow stoichiometry tolerances of finished ceramics. The existing literature provided a guide to the production of high quality BaZrO3, but was not sufficiently complete to readily allow production of crucibles suitable for this application. The two basic aims of this project were: To provide a comprehensive and quantitative description of the necessary attributes of crucibles for barium cuprate melt processing and to expand the knowledge of solid-state BaZrO3 processing to encourage its widespread application to crucible manufacture; To explore the application of solution chemical processes whose potential benefits could lead to routine application of BaZrO3 through improved ceramic quality and processing properties.Based primarily on solid-state processing research, the optimal stoichiometry for corrosion resistant crucibles was observed over the narrow range of 1.003±0.003 Ba : (Zr + Ht) mole ratio. Residual ZrO2 must be strictly avoided even at very low levels because severe localized expansion of Z a grains during reaction with the melt severely reduces corrosion resistance. Although the effect of Ba-rich phases are less severe, their abundance must be suppressed as much as allowed by the production process. Solid-state derived crucibles with a large barium excess were unstable and readily attacked by water. TEM analysis clearly showed residual Zr02 was present as discrete grains and not as grain boundary films, and also the prevalence of intragranular defects in Ba-rich ceramics. Quantitative knowledge of the narrow range of required stoichiometry is critical for developing successful solid-state and solution chemical processes. Reliably achieving the required stoichiometry and phase purity is experimentally challenging and beyond the capability of many processing systems. Systematic investigation revealed sharp changes in physical properties of processed powders across the phase boundary. The resistance of BaZrO3, of the desired stoichiometry to grain growth during powder processing has not previously been reported in the available literature. At the desired stoichiometry for corrosion resistance, powder grain growth resistance combined with very precise control over stoichiometry makes the solid-state process more competitive with solution-based processes than previously acknowledged in the literature. The development of solution processes for BaZr03 precursors is complicated by aqueous chemistry of zirconium compounds.This project developed the first chemically derived precursor process demonstrated to produce a ceramic of adequate quality for sustained barium cuprate melt containment. The barium acetate / zirconium oxychloride / ammonium oxalate system provided control over stoichiometry without requiring elevated solution temperatures, a large excess of barium reagents, or reagents containing alkalis. Despite showing the capability to supersede the solid-state process, the oxalate process still requires further refinement to more reliably achieve high sintered densities. Although the attributes required for sustained barium cuprate melt containment are now clear, its routine mass production remains reliant on further development of solution chemical techniques or improvements to the kinetics of solid-state processing. This project advanced ceramic design and processing technology in the BaZrO3 system and provided new approaches in meeting the challenging analytical needs of research and process control for high quality production of this compound.